ANALISIS PENGARUH SIKAP PETERNAK TERHADAP KEMAMPUAN BERWIRAUSAHA PENGGEMUKAN DAN PEMBIBITAN SAPI DI KECAMATAN PADEMAWU KABUPATEN PAMEKASAN - Puput Puspita Purwasari; Aminah Happy Moninthofa Ariyani; Taufik Rizal Dwi Adi Nugroho (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
Pamekasan Regency has the lowest cattle population in Madura, 194,283 heads. The attitude of farmers who have an important role in the cattle business. This study aims to determine 1) the entrepreneurial characteristics of farmers, 2) the attributes of the dominant attitudes of farmers, and 3) the relationship between the attitudes of farmers and their entrepreneurial abilities in Pademawu District, Pamekasan Regency. The method used is descriptive quantitative, using secondary and primary data from 35 cattle breeders. This study uses a descriptive analysis and multi-attribute Fishbein. The results of this study indicate that 1) the entrepreneurial characteristics of breeders are still common, and their entrepreneurial skills are still low; 2) the dominant attitude of farmers in entrepreneurship is the selling price of farmers, while the attitude that has the lowest rank is maintenance; 3) the relationship between attitudes and abilities in entrepreneurship of breeders is said to be quite close, entrepreneurial attitudes of breeders such as motivation, yield orientation, risk-taking, opportunity utilization and perceptions of livestock business are not dominant attributes, but have a large enough effect. Cattle breeders in Pademawu District need counseling about maintenance risks, financial management, opportunity utilization, yield orientation, and increased motivation.